Assessment of sleep quality in school children of 6-12 years in COVID-19 pandemic - Desai, Palak Y.; Borkar, Pradeep (International Journal of Research in Medical Sciences, 2021)
Background: Sleep disorders in children are one of the common disorders and their frequency has increased during the COVID-19 pandemic. The study aims to assess the quality of sleep and study the parameters of sleep in school children aged 6-12 years in pandemic with the help of children’s sleep habit questionnaire (CSHQ). Methods: A survey-based study was conducted from December 2020 to March 2021 using the data obtained from CSHQ. The study involved 498 school children, among which 244 were male participants and 254 were female participants. It involved students from schools of Rahata and Mumbai, Maharashtra. Results: The results of the study were withdrawn. Bedtime Resistance had mean value of 11.79±4.56, sleep onset delay had mean of 1.56±0.71. Average of sleep duration was 4.56±2.09. Sleep anxiety had mean of 7.48±3.1, night wakings had mean of 4.27±1.91. Mean of parasomnias was 10.1±4.46. Average of sleep disordered breathing was 4.09±1.86, for daytime sleepiness mean was 13.04±5.44 with significance of p˂0.0001. Conclusions: The study concluded that sleep time became lesser and bedtime became later in present scenario of COVID-19. The subscale items of CSHQ scale have increased values indicating towards altered sleep pattern. The total scoring of CSHQ for age group 6-9 years on average is higher than age group 10-12 years except “sleep onset delay” and “sleep duration”. Also, the total scores of female participants are higher as compared to male participants.